Bonding in phase change materials: concepts and misconceptions. (20th March 2018) - Jones, R O
Abstract: Bonding concepts originating in chemistry are surveyed from a condensed matter perspective, beginning around 1850 with 'valence' and the word 'bond' itself. The analysis of chemical data in the 19th century resulted in astonishing progress in understanding the connectivity and stereochemistry of molecules, almost without input from physicists until the development of quantum mechanics in 1925 and afterwards. The valence bond method popularized by Pauling and the molecular orbital methods of Hund, Mulliken, Bloch, and Hückel play major roles in the subsequent development, as does the central part played by the kinetic energy in covalent bonding (Ruedenberg and others). 'Metallic' (free electron) and related approaches, including pseudopotential and density functional theories, have been remarkably successful in understanding structures and bonding in molecules and solids. We discuss these concepts in the context of phase change materials, which involve the rapid and reversible transition between amorphous and crystalline states, and note the confusion that some have caused, in particular 'resonance' and 'resonant bonding'.